Need analysis to develop a preventive curriculum of opisthorchiasis and cholangiocarcinoma for Grade 10 students, in three provinces near the basin of the Northeast Region, Thailand - เลิศวิทยากุล, ธิดารัตน์; เนตรถนอมศักดิ์, ธีรชัย; ลอยลม, วัชรินทร์ (Disease Control Journal, 2018)
The objective of this study was to determine the baseline data on community health problems associated with liver fluke and cholangiocarcinoma with respect to knowledge, understanding, attitudes and belief, food consumption behaviors, and community circumstances. The data obtained from the study were analyzed to identify the need for the development of a curriculum for prevention of liver fluke and cholangiocarcinoma among grade 10 students. Key informants included school administrators, teachers, grade 10 students, parents, community leaders, and health personnel in the areas with high prevalence of liver fluke and cholangiocarcinoma, which are located in the three northeastern river basins, namely the Moon basin (Surin Province), the Chee basin (Roi Et Province) and the Songkram basin (Nakhon Phanom Province). Qualitative study was conducted using focus group discussion. Study tools included focus group discussion, data analysis by means of statistical content analysis. The results were as follows: all of the key informants acknowledged the need for the development of this curriculum. The investigators have therefore summarized key considerations related to the development of curriculum as follows: (1) The curriculum to be developed; (2) Knowledge and the habit of eating uncooked food; (3) The status of course and instruction management; (4) The prospects of collaboration from the community; and (5) The development of the school teachers and collaboration networks.